2023
DOI: 10.1108/jme-09-2023-0093
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative international online learning for the development of intercultural awareness: an experience with pre-service language teachers

Cristina A. Huertas-Abril,
Francisco Javier Palacios-Hidalgo

Abstract: Purpose Considering the potential of Collaborative International Online Learning (COIL) for cross-boundaries interacting and collaborating effectively, this study aims to explore the intercultural awareness of pre-service language teachers after participating in a COIL project. Design/methodology/approach Following a quantitative research approach and an exploratory cross-sectional method, the authors administered a 13-item questionnaire to unveil the perceptions of 64 future language teachers from Spain aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…One of the challenges of ICC development lies in the lack of cultural awareness and interactions with people from other cultures. Recent studies address the promotion of language learners’ ICC through computer-mediated interventions, such as online discussion forums, text-based chat, blogging, email exchanges, social media, video communications and virtual/augmented reality (Elola and Oskoz, 2008; Huertas-Abril and Palacios-Hidalgo, 2023; Lee and Song, 2020; Liu et al , 2023; Jauregi, 2016; Taguchi, 2023; Xu, 2017; Uzum et al , 2023). Most technologies implemented in ICC studies through language acquisition focus on creating and sharing content as well as promoting communication among groups (Shadiev and Sintawati, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges of ICC development lies in the lack of cultural awareness and interactions with people from other cultures. Recent studies address the promotion of language learners’ ICC through computer-mediated interventions, such as online discussion forums, text-based chat, blogging, email exchanges, social media, video communications and virtual/augmented reality (Elola and Oskoz, 2008; Huertas-Abril and Palacios-Hidalgo, 2023; Lee and Song, 2020; Liu et al , 2023; Jauregi, 2016; Taguchi, 2023; Xu, 2017; Uzum et al , 2023). Most technologies implemented in ICC studies through language acquisition focus on creating and sharing content as well as promoting communication among groups (Shadiev and Sintawati, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Shadiev et al ’s (2019) study, students from 13 countries showed a positive perception of using speech-enabled language translation technology to develop their cross-cultural understanding and intercultural sensitivity. Huertas-Abril and Palacios-Hidalgo (2023) suggested that collaborative international online learning is an effective approach to engage learners’ intercultural awareness and cross-cultural engagement.…”
Section: Literature Reviewmentioning
confidence: 99%